The percutaneous absorption of soman in a damaged skin porcine model and the evaluation of WoundStat™ as a topical decontaminant. (3rd April 2018) - Dalton, Christopher; Hall, Charlotte; Lydon, Helen; Jenner, John; Chipman, J. Kevin; Graham, John S.; Chilcott, Robert P.
Abstract: Purpose: The aim of this study was to evaluate a candidate haemostat (WoundStat™), down-selected from previous in vitro studies, for efficacy as a potential skin decontaminant against the chemical warfare agent pinacoyl methylfluorophosphonate (Soman, GD) using an in vivo pig model. Materials and methods: An area of approximately 3 cm 2 was dermatomed from the dorsal ear skin to a nominal depth of 100 µm. A discrete droplet of 14 C-GD (300 µg kg −1 ) was applied directly onto the surface of the damaged skin at the centre of the dosing site. Animals assigned to the treatment group were given a 2 g application of WoundStat™ 30 s after GD challenge. The decontamination efficacy of WoundStat™ against GD was measured by the direct quantification of the distribution of 14 C-GD, as well as routine determination of whole blood cholinesterase and physiological measurements. Results: WoundStat™ sequestered approximately 70% of the applied 14 C-GD. Internal radiolabel recovery from treated animals was approximately 1% of the initially applied dose. Whole blood cholinesterase levels decreased to less than 10% of the original value by 15 min post WoundStat™ treatment and gradually decreased until the onset of apnoea or until euthanasia. All treated animals showed signs of GD intoxication that could be grouped into early (mastication, fasciculations and tremor), intermediate (miosis, salivation and nasal secretions) and late onset (lacrimation, body spasm and apnoea) effects. Two of the six WoundStat™ treated animals survived the study duration. Conclusions: The current study has shown that the use of WoundStat™ as a decontaminant on damaged pig ear skin was unable to fully protect against GD toxicity. Importantly, the findings indicate that the use of WoundStat™ in GD contaminated wounds would not exacerbate GD toxicity. These data suggest that absorbent haemostatic products may offer some limited functionality as wound decontaminants.